Jan Stanisław Żak (1870–1943) – proboszcz w Szadku - Żak, Jan Stanisław (Biuletyn Szadkowski, 2008)
Father Jan Stanisław Żak (1870–1943), priest in Włocławek diocese, was a well- known social worker, actively engaged in efforts aimed at regaining independence by Poland, founder of a printing house and a bookshop in Włocławek. Released from German imprisonment undertakes pastoral work as vicar in three successive parishes near Sieradz, which lasted 19 years, of which 11 years (1923–1934) were spent in Szadek. During his stay in Szadek Father Żak was very active in many areas apart from his pastoral work. He had the parish church restored and the altars renovated, and was very actively engaged in social work such as membership of numerous committees, institutions and organisations, and supervision of Catholic youth organisations and parish library.As a result of increasing conflicts with the parishioners he resigned from Szadek parish and moved in 1934 to the vicarage in Błaszki.